Analisis dan Penanggulangan Network Speed Terhadap Kenyamanan Mahasiswa di Universitas Muhammadiyah Surabaya - Putri Affandi Mussa, Anitya; Haryanti, Tining (Nucleus Journal, 2022)
The problem with University of Muhammadiyah Surabaya students in accessing the Internet is that the network strength is slow or unstable. This study aims to analyze this problem by collecting responses and expectations from students regarding network speed at the University of Muhammadiyah Surabaya. This is not only done to find out students' responses and expectations regarding internet stability at universities, but also to make it easier for campuses to provide solutions to this problem, one of which is to make this research a basis for proposing additional router installation at various dense points of internet network users. in universities, with the hope that the problem of slow Internet networks at the University of Muhammadiyah Surabaya can be overcome. The solution must meet specifications in order to run effectively and efficiently. The Black Box method is an intuitive/imagining thinking method in which the design goals are not determined with certainty. In this study, the examiner will test the network speed using speedtest.net in order to get a sample of the internet network and provide an overview of the router installation that will be installed at the University of Muhammadiyah Surabaya